Analysis of a Mathematical Model for Malaria Transmission with Vaccination Parameter - K., Adamu A.; W., Barde; M., Bulus S.; D., Yavalah (Mikailalsys Journal of Mathematics and Statistics, 2025)
Malaria remains a significant global health challenge, particularly in tropical regions. In this study, we extended the existing compartmental model of S. O. Adewale et al, (2017) by incorporating a vaccination parameter. We established the positivity of solutions, existence and uniqueness of solutions, and analyze the disease-free equilibrium (DFE). The basic reproduction number is derived using the next-generation matrix method, and local/global stability conditions were established. Numerical simulations were carried out to determine the impact of vaccination on the transmission dynamics of the disease. Our findings provide insights into effective malaria control strategies. Also, the result shows that effective vaccination can drastically eradicate the scourge of malaria within the shortest period of time.